Knowledge as Explanandum: Disentangling Lay and Professional Perspectives on Science and Religion. (December 2018) - Kaden, Tom; Jones, Stephen; Catto, Rebecca; Elsdon-Baker, Fern
Issues pertaining to the relationship between science and religion, like creationism, Intelligent Design, and New Atheism, are increasingly the focus of social scientific research. This research often does not differentiate clearly between different kinds of social actors. At the most basic level, professional developers and distributors of systems of thought that deal with the relationship between science and religion, and laypeople who take up this knowledge, or parts of it, must be distinguished. Based upon interview material from the large, multinational study Science and Religion: Exploring the Spectrum, we identify five typical dimensions of lay knowledge vis-à-vis professional knowledge: reinterpretation of professional labels; neglect of important parts of knowledge systems; addition of knowledge; lower ascription of relevance; and an individual ethical framing.